APLIKASI PENERIMAAN PESERTA DIDIK BARU (PPDB) BERBASIS WEBSITE PADA SMAN 1 GUNUNG MEGANG MENGGUNAKAN KONSEP MVC - Merry Agustina; Dendy Mandela (Jurnal Ilmiah Matrik, 2022)
The development of technology is currently growing very fast so the need for fast and efficient information is mandatory. One form of information technology that is widely used to share information is a website. The process of accepting new students (PPDB) carried out by SMAN 1 Gunung Megang is currently still done manually, still using forms so that there are often problems from slow data input, registration files that are not neatly arranged, long registration queues and prospective students sometimes difficulty getting information about the school and the registration process. For that we need information technology in the form of a school website that can assist in the PPDB process at SMAN 1 Gunung Megang.Based on the background of the problem above, a web-based PPDB system was built using the MVC (code) concept and the waterfall method, which has several stages, namely analysis, design, implementation, testing, and maintenance.